Incidence of Deep Vein Thrombosis (DVT) in Patients Using A Knee Scooter. Issue 1 (January 2022) - Davidson, Stuart; Pogorzelski, Nina; Dowd, Thomas C.; Huh, Jeannie
Category: Ankle; Trauma Introduction/Purpose: Functional limitations after lower extremity injury often require the use of an assistive device such as a knee scooter. Many patients find these devices to be easier and more comfortable to use than crutches or walkers. There is concern regarding the possible correlation between scooter use and DVT. Prior literature demonstrated decreased venous flow with the knee flexed, and venous stasis is a known risk factor for DVT 1-3 . Further, healthy volunteers using a scooter demonstrated a significant decrease in volumetric blood flow rate at the popliteal fossa 4 . We report the incidence of DVTs after prescription of a scooter following lower extremity injury. We hypothesized that DVT rates would be higher in patients using a scooter compared to rates of DVT in the NSQIP database Methods: A retrospective record review of adult patients age 18-74 within the Military Health System (MHS) database between 2010-2020 was completed to identify the total number of patients who were prescribed a knee scooter and those who subsequently developed a DVT. Additional demographic and clinical data were collected on patients who had both a scooter and a DVT. This was compared with recorded 2015 NSQIP data on DVT incidence in major orthopaedic surgery procedures. Results: Between 2010 and 2020, 46, 840 of patients within the MHS database were prescribed a rolling scooter after a lower extremity injury or surgery. Of those patients who were prescribed a scooter, 377 subsequently developed a DVT within 90 days of prescription. DVTs were diagnosed on average 26.5 days after scooter prescription. The incidence of DVT of in this population was 0.8%. Conclusion: In the Military Health System database, the use of a knee scooter following lower extremity injury or surgery is associated with a higher incidence of DVT compared to the 2015 NSQIPS incidence of DVT following major orthopedic surgery (0.80% vs 0.55%), and is most frequently diagnosed within 30 days of scooter prescription. Higher level study is needed to confirm these findings and identify risk factors of patients who experience DVTs associated with scooter use after lower extremity injury or surgery.